Developing, Testing, and Communicating Earthquake Forecasts: Current Practices and Future Directions - Mizrahi L; Dallo I; van der Elst NJ; Christophersen A; Spassiani I; Werner MJ; Iturrieta P; Bayona J; Iervolino I; Schneider M; Page MT; Zhuang J; et al. (American Geophysical Union, 2024)
While deterministically predicting the time and location of earthquakes remains impossible, earthquake forecasting models can provide estimates of the probabilities of earthquakes occurring within some region over time. To enable informed decision-making of civil protection, governmental agencies, or the public, Operational Earthquake Forecasting (OEF) systems aim to provide authoritative earthquake forecasts based on current earthquake activity in near-real time. Establishing OEF systems involves several nontrivial choices. This review captures the current state of OEF worldwide and analyzes expert recommendations on the development, testing, and communication of earthquake forecasts. An introductory summary of OEF-related research is followed by a description of OEF systems in Italy, New Zealand, and the United States. Combined, these two parts provide an informative and transparent snapshot of today's OEF landscape. In Section 4, we analyze the results of an expert elicitation that was conducted to seek guidance for the establishment of OEF systems. The elicitation identifies consensus and dissent on OEF issues among a non-representative group of 20 international earthquake forecasting experts. While the experts agree that communication products should be developed in collaboration with the forecast user groups, they disagree on whether forecasting models and testing methods should be user-dependent. No recommendations of strict model requirements could be elicited, but benchmark comparisons, prospective testing, reproducibility, and transparency are encouraged. Section 5 gives an outlook on the future of OEF. Besides covering recent research on earthquake forecasting model development and testing, upcoming OEF initiatives are described in the context of the expert elicitation findings.
Keywords: We capture the state of earthquake forecasting systems in Italy, New Zealand, and the United States, and future plans in these and other countries; Experts encourage benchmark comparison, prospective testing, reproducibility and transparency, but avoid endorsing specific models or tests; Experts stress the need to co-design forecast communication products with end-users to ensure their societal relevance and usefulness